Uruguay - Policy Options for Improving the Efficiency of Uruguay’s Railway Sector : Consolidated Report - World Bank (World Bank, 2012)
The aim of this paper is to review the state of the productive infrastructure of Uruguay and the development policies that govern it and to propose policy options for the long term contribution to achieving a higher level of economic and sustainable development, based on the premise that there is a link between the development of a country's infrastructure and its economic growth. The study analyzes the institutions and pertinent regulations. The study examines in greater depth the factors related to infrastructure production that affect the country in a quantum leap in economic growth. The first study concludes that while no one can assert that the sectors of Uruguay's electricity and transportation are inefficient, there are potential sectoral gains. The policy options have been framed by strategic pillars for each sector and can be summarized as follows: Increase the capacity of transport infrastructure and land ports. Maximize efficiency in providing service transport. Strengthen efficient allocation of resources through a multimodal vision. Improve efficiency and regulation. Position as a logistics center in Uruguay the MERCOSLJR. Therefore, the objective of this study is to review the policies in the areas of Uruguay's productive infrastucture that can have a major impact on the productive structure of the country and hence on economic growth, and hence propose elements and policy options for sectors in the long term.